2021
DOI: 10.1038/s41598-021-81813-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucose confers protection to Escherichia coli against contact killing by Vibrio cholerae

Abstract: Evolutionary arms races are broadly prevalent among organisms including bacteria, which have evolved defensive strategies against various attackers. A common microbial aggression mechanism is the type VI secretion system (T6SS), a contact-dependent bacterial weapon used to deliver toxic effector proteins into adjacent target cells. Sibling cells constitutively express immunity proteins that neutralize effectors. However, less is known about factors that protect non-sibling bacteria from T6SS attacks independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…E. coli are commonly used as prey cells to measure the activity of T6SSs and we previously examined how specific gene knockouts can drastically reduce E. coli survival against the V. cholerae T6SS effectors, TseH and TseL (7, 8). Other groups have also identified genes that influence E. coli survival against T6SSs, including mutants in clpP or crp genes, which were resistant to the T6SS of Agrobacterium tumefaciens or V. cholerae , respectively (19, 29). Cumulatively, these works provide a set of genes with known roles in T6SS survival, which serve as positive controls for identifying important genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli are commonly used as prey cells to measure the activity of T6SSs and we previously examined how specific gene knockouts can drastically reduce E. coli survival against the V. cholerae T6SS effectors, TseH and TseL (7, 8). Other groups have also identified genes that influence E. coli survival against T6SSs, including mutants in clpP or crp genes, which were resistant to the T6SS of Agrobacterium tumefaciens or V. cholerae , respectively (19, 29). Cumulatively, these works provide a set of genes with known roles in T6SS survival, which serve as positive controls for identifying important genes.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic state of the prey cell can also have a profound influence on survival: Stationary phase prey can be more susceptible to attacks due to their decreased ability to form microcolonies isolated from attackers, replace damaged components or produce sufficient immunity proteins for protection (7,11,12,(26)(27)(28). Finally, catabolite repression is another mechanism recently shown to influence E. coli survival against a T6SS attack, where growth with glucose or using mutant prey lacking the cAMP receptor protein (CRP) showed improved survival against the T6SS of Vibrio cholerae strain C6706 (29).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence or absence of certain genes (such as the caseinolytic protease genes clpP and clpA , or the disulfide bond formation gene dsbA ) can also increase a strain’s susceptibility to T6SS attacks ( Lin et al, 2019 ; Mariano et al, 2019 ). Even the simple addition of glucose to the growth medium can have drastic effects on competition ( Crisan et al, 2021 ). As such, although an important component, E-I module composition alone is obviously not the sole deciding factor determining the outcome of T6SS-mediated competition, or competition as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…2C ). We recently reported that target E. coli cells are protected against T6SS attacks from strain C6706* when cocultured on LB medium supplemented with 0.4% glucose ( 4 ). By contrast, we observed that killer C6706*/pAux4 cells bypass the glucose-mediated resistance and efficiently eliminate E. coli cells when the coculture is performed on LB medium with glucose ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells with an active T6SS (“killer cells” here) translocate toxic protein effectors into adjacent target cells. However, the outcome of T6SS-mediated aggression is influenced by the presence of immunity proteins in target cells, the external environment, and target cell stress responses ( 4 7 ). The harpoon-like proteinaceous apparatus is anchored to the membrane of killer cells by the membrane complex, which spans the inner membrane and periplasm ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%